2017
DOI: 10.1111/efp.12395
|View full text |Cite
|
Sign up to set email alerts
|

Association of Eucalyptus globulus leaf anatomy with susceptibility to Teratosphaeria leaf disease

Abstract: Resistance of Eucalyptus globulus juvenile foliage to Teratosphaeria leaf disease (TLD) damage has been shown to be under genetic control. Constitutive traits of juvenile leaves such as stomatal density (counted with wax on and with wax removed), total phenolics, total leaf wax, leaf mass per area (LMA) and leaf anatomical features were assessed to determine differences between pairs of resistant and susceptible families.Anatomic features assessed included cuticle, epidermis, palisade spongy mesophyll and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Indeed, increased susceptibility to A. psidii in populations originating from wetter areas, where disease risk would be expected to be higher, was also reported in E. cloeziana in Queensland (Lee et al ., ), consistent with preadaptation to precipitation gradients influencing susceptibility at the population level. Such preadaptation could impact susceptibility to specific pathogens and involve constitutive morphological, anatomical or chemical traits (Niinemets, ; Smith et al ., , ; Close et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased susceptibility to A. psidii in populations originating from wetter areas, where disease risk would be expected to be higher, was also reported in E. cloeziana in Queensland (Lee et al ., ), consistent with preadaptation to precipitation gradients influencing susceptibility at the population level. Such preadaptation could impact susceptibility to specific pathogens and involve constitutive morphological, anatomical or chemical traits (Niinemets, ; Smith et al ., , ; Close et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Productivity of "eucalyptus" plantations is affected by defoliation levels higher than 25% in the presence of Pseudoteratosphaeria spp. (Lundquist 1987;Smith et al 2018), reaching up to 75% in some cases (Hunter et al 2009). Consequently, this plant material may serve as an inoculation source to infect healthy leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have concluded that pathogen resistance and thicker, denser mesophyll tissue were linked together [16,36,37]. The study's data focused on the measured tissue layers' size but not on individual cell sizes and density.…”
Section: Leaf Morphologymentioning
confidence: 99%
“…A high LMA can mean a thicker epidermis or mesophyll layer in leaves [15], contributing to leaf density. Denser leaves with less intracellular space are related to plant resistance to pathogens-tightly packed cells make it harder for a pathogen to advance into the plant's tissue [16].…”
Section: Introductionmentioning
confidence: 99%